Design and Pore Properties Tuning of Two‐Scale Porous Polyimide Fabricated by Isostatic Pressing for Improving Oil Storage and Tribological Properties. Issue 8 (7th December 2022) - Xu, Mingkun; Guo, Lihe; Ruan, Hongwei; Zhou, Ningning; Yang, Lijun; Wang, Chao; Wang, Tingmei; Qing, Tao; Zhang, Jiyang; Wang, Qihua; Fu, Yizheng; Tao, Liming
Abstract : The development of smart lubricating materials with lasting lubrication and outstanding wear resistance while achieving speed response is of great significance in the field of bearing cage applications but has proven to be challenging. Herein, polyimide (PI) molding powder containing two kinds of PI with different rigidities is synthesized in situ to fabricate a two‐scale porous polyimide (PPI) by (cold and hot) isostatic pressing. The unique two‐scale porous structure originates from the bimodal particle size distribution of the PI molding powder. The oil stored in the two‐scale PPI is gradually thrown out as the rotation speed increases, which makes the two‐scale PPI suitable for bearing cages with a wider rotation speed range and realize persistent and stable oil supply under different speeds. The porosity of PPI decreases with increasing pressure during hot isostatic pressing, but the effect of temperature on the porosity is not obvious. Moreover, the two‐scale PPI maintains good mechanical properties, and its ring tension is as high as 22.3 MPa. Due to the high oil content (>15%) and excellent oil retention rate (93.3%, at 3000 rpm for 180 min), the two‐scale oil‐containing PPI exhibits a stable low friction coefficient (≈0.096) and ultralow wear rate (≈0.68 × 10 −6 mm 3  (Nm) −1 ). Abstract : A two‐scale porous polyimide with high oil content (>15%) and excellent oil retention rate (93.3%, at 3000 rpm for 180 min) is fabricated by synthesizing in situ polyimide powder with different rigidities macromolecules and isostatic pressing, which is suitable for bearing cages with a wider rotation speed range and realizes persistent and stable oil supply under different speeds.